The role of self-regulated learning on foreign vocabulary learning: a multi-case study - Baihaqi Zakaria Muslim; Moh. Arif Mahbub (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
In recent years, a considerable body of empirical research has acknowledged the role of self-regulated learning (henceforth SRL) in the domain of English as a foreign language (EFL). However, the study investigating the role and mechanism of SRL in vocabulary learning is still in scarcity particularly in Indonesian contexts. To address this noticeable gap, this multi-case study aims to explore the role of SRL on vocabulary learning strategies use and mechanism from the experience of undergraduate EFL learners. After signing the informed of consent form sheets, two undergraduate students from two different countries (Indonesia and Egypt) voluntarily participate in this study. By employing a series of semi-structured interviews and conducting narrative thematic analysis (Braun & Clarke, 2006), the findings showcase that both participants employ a myriad of vocabulary learning strategies such as rehearsal, elaboration, and social strategy. Additionally, the empirical evidence indicates that they have higher level of motivation and persistence to maintain vocabulary-learning activity. The findings suggest the important practical implications for teachers, learners, and institution. This article also discusses limitations and recommendations.